2018
DOI: 10.1002/wene.324
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the risks of induced seismicity in subsurface energy operations

Abstract: Shale gas could help address the insatiable global demand for energy. However, in addition to risks of environmental pollution, the risk of induced seismicity during the hydraulic fracturing process is often considered as the major showstopper in the public acceptability of shale gas as an alternative source of fossil fuel. Other types of subsurface energy development have also demonstrated similar induced seismicity risks. This article presents an interdisciplinary review of notable cases of suspected induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…However, to decide injection rates one should also consider possible risks of induced seismicity, as it has been reported that injecting water in the subsurface with high flow rates could trigger seismic events. 134 Excluding safety and technical feasibility considerations, increasing the injection rate could shorten the duration of the project, anticipating possible revenues expected form the carbon tax. Analysis on the sensitivity of NPV and IRR on this parameter has not been conducted herein, but it could be done with straightforward modifications of the model developed here.…”
Section: Resultsmentioning
confidence: 99%
“…However, to decide injection rates one should also consider possible risks of induced seismicity, as it has been reported that injecting water in the subsurface with high flow rates could trigger seismic events. 134 Excluding safety and technical feasibility considerations, increasing the injection rate could shorten the duration of the project, anticipating possible revenues expected form the carbon tax. Analysis on the sensitivity of NPV and IRR on this parameter has not been conducted herein, but it could be done with straightforward modifications of the model developed here.…”
Section: Resultsmentioning
confidence: 99%
“…In each of the stages broadly identified in Figure 5 , aggressive research and development programs have contributed to the long-term success of both the energy and chemicals industries for many generations. Prior innovations have led to, e.g., identifying previously unknown hydrocarbon reservoirs, 65 producing unconventional hydrocarbons such as shale gas, 66 reducing the risks associated with production 67 and transport, 68 new energy-efficient separation processes (e.g., membrane separations), 69 , 70 new catalytic processes, 71 and process intensification. 72 Despite frequent changes in priorities due to the fast-changing socioeconomic landscape, as demonstrated by the high level of attention to hydrogen production and utilization that has affected the energy industry over the past 12–24 months, 73 research in the various stages summarized in Figure 5 remains critical.…”
Section: Some Research Opportunitiesmentioning
confidence: 99%